2017
DOI: 10.3389/fmicb.2017.01519
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Histopathological and Ultrastructural Changes in Channel Catfish Experimentally Infected with Virulent Aeromonas hydrophila

Abstract: A highly virulent clonal population of Aeromonas hydrophila (vAh) has been the cause of recent motile Aeromonas septicemia epizootic in channel catfish (Ictalurus punctatus) farms in the Southeastern United States. The pathology of the disease caused by vAh has not been studied well yet. Thus, our aim was to determine histopathological and ultrastructural changes in channel catfish following vAh challenge. To accomplish this, catfish fingerlings were challenged with vAh (strain ML09-119) by bath. Six fish per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
35
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 27 publications
14
35
1
1
Order By: Relevance
“…These pigmented cells may appear isolated or in the form of a cluster where it indicates the positive presence of neutral carbohydrate and melanin (Agius & Roberts, ). Our results were much like the findings found in other fish species in previous investigations (Abdelhamed, Ibrahim, Baumgartner, Lawrence, & Karsi, ; Brenden & Huizinga, ; Cipriano, Bullock, & Pyle, ; Kumar et al, ; Stratev, Stoev, Vashin, & Daskalov, ).…”
Section: Discussionsupporting
confidence: 92%
“…These pigmented cells may appear isolated or in the form of a cluster where it indicates the positive presence of neutral carbohydrate and melanin (Agius & Roberts, ). Our results were much like the findings found in other fish species in previous investigations (Abdelhamed, Ibrahim, Baumgartner, Lawrence, & Karsi, ; Brenden & Huizinga, ; Cipriano, Bullock, & Pyle, ; Kumar et al, ; Stratev, Stoev, Vashin, & Daskalov, ).…”
Section: Discussionsupporting
confidence: 92%
“…hydrophila interaction. Another study in channel catfish, focusing on histological changes, showed lesions to appear first in the stomach and spleen, then in the intestine, and only after that on the gills [56]. Thus, in channel catfish, the adherence of A .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in channel catfish, the adherence of A . hydrophila to mucins shows an inverse relationship with the pathological signs [55, 56]. This inverse relationship could be explained by the mucins potentially acting as releasable decoys, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At 3 weeks post-immunization, catfish were experimentally infected by bath immersion with 2.8 × 10 10 CFU/ml of A. hydrophila ML09-119 for 6 h at 30°C (17). Bacterial infection dose was chosen based on previous experimental infection doses (8, 18). Bacteria numbers (CFU/ml) in the overnight cultures were determined by plating serial 10-fold dilutions on agar plates followed by viable colony counts.…”
Section: Methodsmentioning
confidence: 99%